ChemInform Abstract: Fast Functionalization of (7‐Aza)indoles Using Continuous Flow Processes. Issue 30 (7th July 2016) - D'Attoma, Joseph; Cozien, Gregoire; Brun, Pierre Louis; Robin, Yves; Bostyn, Stephane; Buron, Frederic; Routier, Sylvain
Abstract: The functionalization of the title compounds proceeds in three steps, namely iodination, nitrogen protection, and copper‐free Sonogashira cross‐coupling reaction by using a continuous flow set‐up.